Immediate Effects of the Schroth Method on Spinal Curvature and Paravertebral Muscle Activation in Adolescent Idiopathic Scoliosis - Xiaohui Zhang; Jinmiao Lv; Xianglan Li; Baiyan Lin; Yinzi Huang; Yan Lin; Min Hu; Bagen Liao (Orthopaedic Surgery)
ABSTRACT Objectives The Schroth method is considered potentially valuable as an alternative intervention to control curve progression in mild to moderate adolescent idiopathic scoliosis. However, patients are often dependent on the subjective experience of the physiotherapist when practicing, as changes in spinal alignment and muscle activation are unknown. The aim of this study was to evaluate the effectiveness of the Schroth method for spinal alignment and muscle activation in adolescents with idiopathic scoliosis (AIS). Methods This prospective cross‐sectional study, conducted at the Scoliosis Engineering Center of Guangzhou Sport University (January 2020–October 2022), enrolled 36 AIS (4 males, 32 females; age 13.2 ± 1.8 years) presenting major thoracic curvature (Cobb angle: 10°–40°, Risser stage 0–4). Participants underwent a standardized 1‐week pretraining protocol before performing four Schroth exercises (“50 × Pezziball,” sail, muscle cylinder, and corrected standing). Real‐time spinal ultrasound angles (SUAs) and paraspinal muscle activation (via surface electromyography, sEMG) were quantified during habitual standing (baseline) and exercise conditions. Normality was verified using Kolmogorov–Smirnov tests. Within‐group comparisons employed paired t‐tests (effect sizes: Cohen's d; 95% CIs), while proximal thoracic (PT) compensation frequencies were assessed via chi‐squared tests. Results All four Schroth exercises significantly reduced the SUA of the primary thoracic curve compared to habitual standing (p < 0.05). The lumbar curve SUA decreased specifically after “50 × Pezziball” and muscle cylinder exercises (p < 0.05). PT curve compensation frequency rose from 16.7% (6/36) in habitual standing to 33.3% (12/36) and 30.6% (11/36) during “50 × Pezziball” and sail exercises, respectively (p < 0.05). sEMG demonstrated reduced paravertebral muscle (PSM) activation asymmetry at the thoracic apex (T8) during corrective standing, “50 × Pezziball,” and sail exercises (p < 0.05). However, “50 × Pezziball” and sail exercises triggered compensatory left‐dominant PSM imbalance at T2 (p < 0.05). At lumbar levels (L2–L5), performing 50 × Pezziball exercise exacerbated asymmetry (p < 0.05), whereas muscle cylinder exercises reversed the activation patterns of the PSM (p < 0.05). Conclusion While Schroth exercises effectively reduced thoracic curvature and improved T8 muscle symmetry, caution is warranted during “50 × Pezziball” and sail exercises due to increased PT compensation and lumbar/T2 muscle imbalances. Muscle cylinder exercises may mitigate adverse lumbar effects.